2017
DOI: 10.30924/mjcmi/2017.22.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The role of bonding and bridging cognitive social capital in shaping entrepreneurial intention in transition economies

Abstract: Entrepreneurship is an important factor of potential growth and development that will determine the development dynamics of transition countries in the future

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
4
10
0
3
Order By: Relevance
“…The results obtained for the main constructs of the TPB model place us in line with other studies where ATB and PBC (Liñán et al 2011a;Vukovic et al 2017) have a high, direct, and positive effect over EI. Our model reveals ATB to be the construct which has the greatest effect over EI in accordance with other studies (Vukovic et al 2017), but no significant differences between the two environments were found (Canever et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…The results obtained for the main constructs of the TPB model place us in line with other studies where ATB and PBC (Liñán et al 2011a;Vukovic et al 2017) have a high, direct, and positive effect over EI. Our model reveals ATB to be the construct which has the greatest effect over EI in accordance with other studies (Vukovic et al 2017), but no significant differences between the two environments were found (Canever et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Besides, entrepreneurship is not only seen as an economic phenomenon, but it is also determined as a social one. Thus, social perspectives are often interested in entrepreneurship researches via some concepts such as social capital, social network, cognitive capital and human capital (Vuković et al, 2017). Indeed, the important role of social capital on forming business start-up intention has been determined in much research, but almost previous researches consider that the concept of social capital either is similarly to human capital or cognitive capital.…”
Section: Introductionmentioning
confidence: 99%
“…The influence and support from close friends and family can be much more crucial than other cultural norms in shaping the cognitive process of entrepreneurship among nascent entrepreneurs and their entrepreneurial self-efficacy (Baughn et al, 2006;Bhagavatula, Elfring, van Tilburg, & van de Bunt, 2010). Vuković, Kedmenec, Postolov, Jovanovski, and Korent (2017) postulate the investigation of correlations between social capital and the cognitive process of a business venture. Hence, I propose the following hypothesis: H7: Social capital positively affects (a) attitude towards entrepreneurship, (b) perceived behavioural control, (c) entrepreneurial self-efficacy and (d) entrepreneurial intention.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…The role of contextual factors on predicting entrepreneurial intention among Vietnamese… | 181 of social capital in shaping entrepreneurial self-efficacy and the cognitive process of business venture (Baughn et al, 2006;Vuković et al, 2017). In terms of the relationship between country institutional profile and the cognitive process of entrepreneurship, the normative dimension is not directly related to entrepreneurial intention but strongly affects the intention to become an entrepreneur through entrepreneurial self-efficacy and perceived behavioural control (γindirect ND-EI = γtotal ND-EI = 0.235).…”
Section: Structural Modelmentioning
confidence: 99%